PERUBAHAN PERSPEKTIF DOMINANT LOGIC DALAM PEMASARAN (Fokus Ekonomi, 2010)
Marketing inherits economic exchange model that have dominant logic which based on good exchange like in manufacture. That dominant logic focuses on tangibles resources, values, and transactions. In the last decade, there is a new perspective that makes a different to counter the competition which focuses on intangible resources, co-create value, and long-term relationship. This paper explains a new dominant logic, how the changes of the perspective happened, and how the new one can be a conceptual based for service science.